Numerical Investigation of Aerodynamic Noise Reduction of Nonpneumatic Tire Using Nonsmooth Riblet Surface - Haichao Zhou; Zhen Jiang; Jian Yang; Huihui Zhai; Guolin Wang (Applied Bionics and Biomechanics)
Unlike conventional pneumatic tires, the nonpneumatic tires (NPT) are explosion proof and simple to maintain and provide low rolling resistance. At high vehicle speeds, however, the complex airflow produced by the open flexible-spoke structure of NPT yields high aerodynamic noise, which contributes to sound pollution in the vehicular traffic environment. Inspired by the idea that a nonsmooth riblet structure can affect fluid flow and offer noise reduction, the analyses of the effect of the nonsmooth riblet surface on the aerodynamic noise of an NPT and noise reduction mechanism were presented in this paper. First, computational fluid dynamics (CFD) was used to analyze the surface pressure coefficient characteristics of a smooth flexible-spoke tire rolling at a speed of 80 km/h and subsequently validating the numerical simulation results by comparing them with published test results. Secondly, large eddy simulation (LES) and the Ffowcs Williams–Hawkings (FW-H) method were, respectively, used to determine the transient flow and far-field aerodynamic noise. Then, the mechanism of noise reduction was investigated using a vortex theory. Based on the vortex theory, the positions and strengths of noise sources were determined using the Lamb vector. Finally, according to the fluid boundary layer theory, a nonsmooth riblet surface was arranged on the surface of the spokes, and the influences of the riblet structure parameters, including size, position, and direction, on aerodynamic noise were analyzed. Based on the vortex theory, it was found that the nonsmooth riblet structure can reduce the Lamb vector, suppress the generation of flow vortices, decrease acoustic source strength, and effectively decrease noise up to 5.18 dB using the optimized riblet structure. The study results provide a theoretical basis for the structural design of a new low-noise NPT.